Working Women in the News: A Study of News Media Representations of Women in the Workforce - Magor, Deborah A (2006)
This study examines how working women are represented in the news media, and its main aim is to determine to what extent ‘social class’ figures in the representations of women in news content. Using language, visual and narrative analysis, the thesis comprises four case studies each focusing on portrayals of different women from different socio-economic backgrounds determined by their occupation. The first two case studies examine portrayals of low paid working women through coverage of the National Minimum Wage introduction into Britain in April 1999 and the Council Workers’ Strike in England and Wales in 2002. The latter two case studies focus on women in particular professions: elite businesswomen, military women and women war reporters. The study concludes by noting that multiple voices occur in news texts around the key contrasting themes of progress/stagnation and visibility/invisibility and which can give contradictory discourses on the intersection of gender and class. From the massification and silencing of working class women, to the celebrity and sexualisation of the business elite, and the professional competency news frames of middle class women, class was shown to be a determining factor in how women figure in news content. However, these class determinants combined with other news frames pertaining to gender, whereby powerful and established myths of femininity can come to the fore. These myths can be particularly powerful when women enter non-feminine work ‘spaces’ such as business and the military, and class, particularly in the latter case, can tend to slip out of view, as sexist coverage is commonplace and debates are formed about the right and wrong behaviour for women